Marks caused by the scavenging activity of Necrobia rufipes (Coleoptera: Cleridae) under laboratory conditions - Zanetti, Noelia Inés (2015)
Insects are an important group involved in carrion consumption and are thus of forensic interest. In the laboratory we studied the taphonomic marks that Necrobia rufipes (Cleridae) can produce. Pig trotters were exposed to adult beetles at 21 ± 3 C and 12:12 h day/night cycle. We made observations and took photographs every 4e5 days for 12 months. Marks were noted after a month. We found scratches, pits, holes, and tunnels in several kinds of tissue such as integumental, connective and muscular. This work contributes preliminary data of significant application in biology, ecology, anthropology and forensics. Until now, no study has provided taphonomic information with N.rufipes